JOB READY GO - BALTI, HAYTHEM (JOHN WILEY, 2022)
Tackle GoLang with practical and employment-focused instruction In Job Ready Go, software education guru Dr. Haythem Balti delivers an essential and hands-on guide to Go, an open-source programming language developed by Google engineers to combine the most sought-after capabilities of other programming languages, including Java, C#, and C++. In the book, the author walks you through all the most critical skills necessary for successful, on-the-job Go programming. You'll discover: How to get started with Go, including how to run, build, and test your own go programs Understand control flow and data structures in Go including arrays, slices, maps, and pointerss How to leverage structs, interfaces, and methods to organize and reuse code How to leverage go to process data, access different types of files and develop APIs Leverage concurrency and gRPCs to create complex and interconnected systems. Job Ready Go offers readers straightforward and elegant instruction based on the renowned mthree Global Academy and Software Guild training program. It's an essential read for aspiring Go developers looking for a fast-track to developing real-world skills demanded by employers.